The Contribution of Rupiah and Kina: An Analysis of Dual Currency Impact on Local Economic Growth in the Skouw Sae Border Area - Nani Hanifah (JOURNAL OF SHARIA ECONOMICS, 2024)
This study explores the utilization of dual currencies, the Indonesian Rupiah and Papua New Guinean Kina, in financial transactions within the Skouw Sae border area. Focusing on cross-border market dynamics, the research identifies the significant impact of dual currency usage on local economic growth, price stability, and community welfare. Employing a qualitative descriptive method, data were collected through interviews with business actors and local residents, participatory observations at Skouw Market, and an analysis of documentation related to cross-border transactions. The findings reveal that the dual currency system enhances market liquidity, broadens access to international markets, and fosters an inclusive trade ecosystem. However, fluctuating exchange rates between the Rupiah and Kina pose a major challenge in determining the pricing of goods and services. Nonetheless, the flexibility of using both currencies simplifies transactions, increases the purchasing power of Papua New Guineans, and strengthens the income of local traders. This study provides valuable insights into how dual currencies can be optimized to support sustainable economic growth in border areas. The implications of this research include policy recommendations to strengthen cross-border trade regulations and improve the exchange rate stability of the two currencies.